Rational Design of Gdp‑D‑Mannose Mannosyl Hydrolase for Microbial L‑Fucose Production - Blamey-Alegria, J (BioMed Central Ltd, 2023)
Background: l‑Fucose is a rare sugar that has beneficial biological activities, and its industrial production is mainly achieved with brown algae through acidic/enzymatic fucoidan hydrolysis and a cumbersome purification process. Fucoidan is synthesized through the condensation of a key substance, guanosine 5′‑diphosphate (GDP)‑l‑fucose. Therefore, a more direct approach for biomanufacturing l‑fucose could be the enzymatic degradation of GDP‑l‑fucose. However, no native enzyme is known to efficiently catalyze this reaction. Therefore, it would be a feasible solution to engineering an enzyme with similar function to hydrolyze GDP‑l‑fucose. Results: Herein, we constructed a de novo l‑fucose synthetic route in Bacillus subtilis by introducing heterologous GDP‑l‑fucose synthesis pathway and engineering GDP‑mannose mannosyl hydrolase (WcaH). WcaH displays a high binding affinity but low catalytic activity for GDP‑l‑fucose, therefore, a substrate simulation‑based structural analysis of the catalytic center was employed for the rational design and mutagenesis of selected positions on WcaH to enhance its GDP‑l‑fucose‑splitting efficiency. Enzyme mutants were evaluated in vivo by inserting them into an artificial metabolic pathway that enabled B. subtilis to yield l‑fucose. WcaHR36Y/N38R was found to produce 1.6 g/L l‑fucose during shake‑flask growth, which was 67.3% higher than that achieved by wild‑type WcaH. The accumulated l‑fucose concentration in a 5 L bioreactor reached 6.4 g/L. Conclusions: In this study, we established a novel microbial engineering platform for the fermentation production of l‑fucose. Additionally, we found an efficient GDP‑mannose mannosyl hydrolase mutant for L‑fucose biosynthesis that directly hydrolyzes GDP‑l‑fucose. The engineered strain system established in this study is expected to provide new solutions for l‑fucose or its high value‑added derivatives production. © 2023, The Author(s).